2022
DOI: 10.3389/fphys.2022.934597
|View full text |Cite
|
Sign up to set email alerts
|

Combined Systemic Intake of K-ATP Opener (Nicorandil) and Mesenchymal Stem Cells Preconditioned With Nicorandil Alleviates Pancreatic Insufficiency in a Model of Bilateral Renal Ischemia/Reperfusion Injury

Abstract: We used nicorandil, a K-ATP channel opener, to study the role of these channels in the amelioration of renal ischemia/reperfusion (I/R)-induced pancreatic injury, and the possible involvement of PI3K/Akt/mTOR signaling pathway. Forty-two male Wistar rats were included in this study, six were sacrificed for extraction of bone marrow mesenchymal stem cells (BM-MSCs) and conducting the in-vitro work, the others were included in vivo study and equally divided into six groups. Group 1 (sham control), but groups 2–6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 53 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…We reported a significant increase concerning the levels of serum glucose in the IR group, indicating that an impaired pancreatic structure was occurred after IR (16). It has been proposed that hyperglycemia induces oxidative stress and decreases endogenous antioxidant enzymes through different mechanisms.…”
Section: Discussionmentioning
confidence: 65%
“…We reported a significant increase concerning the levels of serum glucose in the IR group, indicating that an impaired pancreatic structure was occurred after IR (16). It has been proposed that hyperglycemia induces oxidative stress and decreases endogenous antioxidant enzymes through different mechanisms.…”
Section: Discussionmentioning
confidence: 65%
“… 18 , 40 In contrast, we reported that pretreatment of MSC with cardioprotective drug is a clinically promising method to enhance the effect of MSC and exosomes on cardiac repair for AMI. 18 , 26 , 27 Since Nicorandil has been proven to have significant effects in protecting cardiac cells, reducing cardiovascular events and directly protecting MSC from apoptosis under H/SD conditions in vitro, 25 , 31 , 32 we used nicorandil as pretreatment drug for MSC in the present study and found that intramyocardial injection of MSC NIC -exo had superior therapeutic effects in cardiac repair post-MI with cardiac function enhanced, infarct size and collagen area minimized, inflammatory cells and cytokines infiltration suppressed, angiogenesispromoted, as well as macrophage M2 polarization facilitated in the infarct region.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Our previous studies found that both treatment with cardioprotective drugs (atorvastatin and Tongxinluo) and the two drug-pretreated MSC could enhance the effects of cardiac repair post-AMI via altering the mRNA or non-coding RNA profiles of their exosomes. 18,26,27 Similar to statins and Tongxinluo, the nicorandil treatment also showed superior cardioprotective effect to MSC alone in heart failure rats [28][29][30][31] and nicorandil-pretreatment could protect MSC from hypoxia/serum-deprivation injury in vitro as well. 31,32 Therefore, we hypothesized that nicorandilpretreated MSC-derived exosomes (MSC NIC -exo) could have distinct non-coding RNA profiles and also better therapeutic effects than MSC-derived exosomes (MSC-exo) in treating AMI.…”
mentioning
confidence: 94%
See 1 more Smart Citation